Peruvian Political Neology in the UNIFE Node of the Observatory of Neology (Pompeu Fabra University) - Period 2003-2019 - Luna García, Rosa (2021)
The main objective of this empirical, applied, documentary and systematic terminographic study was to determine the productivity of Peruvian political neologisms collected in the Peruvian node UNIFE of the Observatory of Neology of the Pompeu Fabra University during the period 2003-2019. The research arrived at the following general conclusions: 1) The low number of tokens (repetitions) in the Peruvian political neological corpus could be attributed to problems in asystematic detection, to the mobility of the neologisms that integrate the Antenas Neológicas Unifé node or to the variability of neological sentiment. The authors Adelstein and Freixa (2013) argued in a research carried out from data provided by the Neology Observatory of the Pompeu Fabra University that these platforms are characterized by the presence of a high number of neologisms with low stabilization. 2) Regarding the annual productivity of political neologisms, a fairly balanced trend was observed between the two octennia of study. The first octenary of the study corpus (2004-2011) reached 42.2 % compared to 57.6 % of the second, with a 15.2 % difference between them. 3) It was found that the criteria used for the dictionarization of neologisms in general language dictionaries (exclusion of local neologisms, ephemeral, derived from proper names and words with transparent productive suffixes [Aldenstein and Freixa, 2013]), differed from those related to the geolectal nature. Several authors have shown that in the latter, factors such as the witness character of new words in a given political period (Matoré, 1953; Aldenstein and Freixa, 2013) or the need to name a new word (Barnhart, 2007), 4) The formal newspapers El Comercio and La República were the most productive in Peruvian political neology, basically concentrated in the political, current affairs, national, editorial page and columns sections. 5) In the coining of Peruvian political neologisms, it was observed that derivation, suffixation and prefixation, together with composition (patrimonial and cultured) reached a high 81.7 %. This result is confirmed in several works on political neology (Díaz, 2001; Cabré, 2006; Camacho, 2010; Aldenstein and Freixa, 2011; Borhn, 2015).